Ashitaba (Angelica keiskei) Leaves Extract Cream 8% Prevented Tyrosinase and Melanin Elevation in the Ultraviolet B-Exposed Guinea Pig (Cavia porcellus) Skin - Erwin Sugito; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Ultraviolet B radiation causes free radical formation, which then activates tyrosinase, an enzyme that plays a role in melanin biosynthesis. The purpose of this study was to prove that Ashitaba (Angelica keiskei) leaves extract cream 8% prevented the increase of tyrosinase levels and the amount of melanin in the ultraviolet B-exposed guinea pig (Cavia porcellus) skin. Methods: This study was conducted with a randomized posttest only control group design. The subjects were guinea pigs (Cavia porcellus), male, healthy, local strains, aged 3-4 months, weighing 300-350 grams, one hybrid, which were divided into 2 groups (n= 18). The control group (ultraviolet B exposure and placebo of basic cream), and the treatment group ultraviolet B exposure and Ashitaba leaves extract cream 8%). After 2 weeks of treatment, tyrosinase levels were examined by the ELISA method, while the amount of melanin was examined using Masson-Fontana staining. Results: The tyrosinase level in the control group was higher than the treatment group. The tyrosinase level of control group was 30.95 ± 3.43 ng/ml while in the treatment group was 11.60 ± 0.34 ng / ml (p <0.05). Similarly, the melanin in the control group was higher than the treatment group. The average number of melanin in the control group was 20.54 ± 2.59% while in the treatment group was 1.96 ± 1.25% (p <0.05). Conclusion: Ashitaba (Angelica keiskei) leaves extract cream 8% prevented the increase of tyrosinase levels and the amount of melanin in the ultraviolet B-exposed guinea pig (Cavia porcellus) skin.